The Parallel Worlds of Christoph Scheiner and Galileo Galilei. (August 2016) - Engvold, Oddbjørn; Zirker, Jack B.
Galileo Galilei and Christoph Scheiner, working independently, discovered many of the properties of sunspots that we accept as valid today. Using his precise drawings of sunspots, Scheiner discovered seasonal variations in the slope of sunspot tracks. These led him to measure a small inclination of the solar axis with respect to the ecliptic plane. Galileo interpreted the variations of sunspot tracks as strong evidence in support of the Copernican model of the planets and Sun. Scheiner, in contrast, sought to reconcile his discoveries with his belief in Church dogma. He rejected the Copernican model and adopted instead Tycho Brahe's hybrid geocentric model, which was consistent with all pertinent observations.